N, N-Bis(glycityl)amines as anti-cancer drugs. Issue 17 (1st September 2016) - Waghorne, Charlotte L.; Corkran, Hilary M.; Hunt-Painter, Alex A.; Niktab, Eliatan; Baty, James W.; Berridge, Michael V.; Munkacsi, Andrew B.; McConnell, Melanie J.; Timmer, Mattie S.M.; Stocker, Bridget L.
Graphical abstract: Abstract: A series of N, N -bis(glycityl)amines with promising anti-cancer activity were prepared via the reductive amination of pentoses and hexoses, and subsequently screened for their ability to selectively inhibit the growth of cancerous versus non-cancerous cells. For the first time, we show that this class of compounds possesses anti-proliferative activity, and, while the selective killing of brain cancer (LN18) cells versus matched (SVG-P12) cells was modest, several of the amines, includingd -arabinitylamine1a andd -fucitylamine1g, exhibited low micromolar IC50 values for HL60 cells. Moreover, these two amines showed good selectivity towards HL60 cells when compared to non-cancerous HEK-293 cells. The compounds also showed low micromolar inhibition of the leukaemic cell line, THP-1. The modes of action of amines1a and1g were then determined using yeast chemical genetics, whereby it was established that both compounds affect similar but distinct sets of biochemical pathways. Notably purine nucleoside monophosphate biosynthesis was identified as an enriched mechanism. The rapid synthesis of the amines and their unique mode of action thus make them attractive targets for further development as anti-cancer drugs.